Profile of unnatural mortality at tertiary hospital. - Syarifah, Mustika Chasanatusy; Kurniasari, Diyan Wahyu (Gaceta Médica de Caracas, 2021)
Introduction: Unnatural deaths are deaths that can be prevented, the frequency of which reflects the quality of public health services. Unnatural deaths occur due to external causes such as suicide, homicide, and accidents. This study aims to analyze the profile of cases of unnatural death at Dr. Soetomo General Hospital, Surabaya, Indonesia.